In Vivo Tibial Fit and Rotational Analysis of a Customized, Patient-Specific TKA versus Off-the-Shelf TKA - Schroeder, Lennart; Martin, Gregory (The Journal of Knee Surgery, 2019)
In total knee arthroplasty (TKA), surgeons often face the decision of maximizing tibial component fit and achieving correct rotational alignment at the same time. Customized implants (CIMs) address this difficulty by aiming to replicate the anatomical joint structure, utilizing data from patient-specific knee geometry during the manufacturing. We intraoperatively compared component fit in four tibial zones of a CIM to that of three different off-the-shelf (OTS) TKA designs in 44 knees. Additionally, we assessed the rotational alignment of the tibia using computed tomography (CT)-based computer aided design model analysis. Overall the CIM device showed significantly better component fit than the OTS TKAs. While 18% of OTS designs presented an implant overhang of 3 mm or more, none of the CIM components did (p < 0.05). There was a larger percentage of CIMs seen with optimal fit (≤1 mm implant overhang to ≤1 mm tibial bone undercoverage) than in OTS TKAs. Also, OTS implants showed significantly more component underhang of ≥3 mm than the CIM design (37 vs. 18%). The rotational analysis revealed that 45% of the OTS tibial components showed a rotational deviation of more than 5 degrees and 4% of more than 10 degrees to a tibial rotational axis described by Cobb et al. No deviation was seen for the CIM, as the device is designed along this axis. Using the medial one-third of the tibial tubercle as the rotational landmark, 95% of the OTS trays demonstrated a rotational deviation of more than 5 degrees and 73% of more than 10 degrees compared with 73% of CIM tibial trays with more than 5 degrees and 27% with more than 10 degrees. Based on our findings, we believe that the CIM TKA provides both better rotational alignment and tibial fit without causing overhang of the tibial tray than the three examined OTS implants.
Keywords: customized implants; implant fit; implant rotation; total knee arthroplasty